O efeito da gratidão na reavaliação cognitiva - Giglio, Ana Carolina Alem (2017)
Some areas of psychology have attempted to understand positive emotions and their relation with cognition. Researches have shown that positive emotions may be related to the broadening of attentional focus and establishment of problem solving repertoire. One of the emotions that has drawn attention in researches, demonstrating cognitive consequences is gratitude, which may be associated with establishing social bonds, increasing well-being and satisfaction in the relationship. Despite the cognitive consequences of this emotion, it is still not clear whether gratitude can facilitate the efficient use of strategies for cognitive control of emotions, and the present paper sought to answer this question. In addition, since gratitude is an emotion with great social impact, this study sought to investigate whether i) sharing with others experiences of gratitude and ii) only writing about such experiences could have a distinct impact on the ability to increase or to decrease an emotion (up and down regulation) using cognitive reappraisal strategy. For this study, 73 participants were divided into three groups: group1 - wrote and shared experiences of gratitude; group2 - only wrote about experiences of gratitude; and group3 - shared experiences without emotional content. The three types of intervention lasted for four weeks. To evaluate the cognitive reappraisal ability, an emotional image trial was performed, in which participants had to use strategies to increase positive emotion, decrease negative emotion or to maintain their naturally elicited emotion. Behavioral measures (valence and intensity, positive / negative affects and gratitude) and physiological measures (skin conductance and heart rate) were performed. The main results showed that the two experimental groups obtained: i) an increase in the gratitude questionnaire score after the intervention; ii) a more efficient use of the cognitive reappraisal strategy in the valence scale. Such results may indicate that both sharing and the simple attention directing to specific situations of gratitude are able to favor the increase of general perception of gratitude of the individual towards his own life and to improve the efficiency of cognitive control strategies of positive and negative emotions. In addition, the group that shared experiences of gratitude increased their level of positive affects, while the group that only wrote about their experiences maintained it; and the control group decreased the level of positive affects. These findings may show gratitude as a background for the perception of other positive stimuli, but sharing has potentiated this effect. There was a decrease in heart rate during the maintenance of elicited emotion in the negative images by group2, referring to the down-regulation strategy, suggesting greater cognitive engagement during reappraisal. These results may indicate that the group that only reported experiences of gratitude may have needed greater cognitive demand to efficiently use the reappraisal strategy compared to group1. The analysis of the content of the reports showed that the words that appeared more on the semantic map of the experimental groups were words with relational content, unlike the control group, indicating that the social relation may be linked to gratitude as an inherent condition.